Exploratory and confirmatory factor analysis of self-efficacy among student-athletes - Firmante, Maria Cristina M. (Animo Repository, 2011)
The study developed an instrument that measures four factors of self-efficacy among student-athletes which were based on Bandura’s sources of self-efficacy theory. The four factors are: Performance accomplishments, modeling, verbal persuasion, and emotional arousal. The survey questionnaire was validated and distributed to 157 student-athletes (N= 157). Out of 157 respondents, 87 were males and 70 were females whose ages range from 16 to 21 years old. The respondents were all from one private tertiary institution in Metro Manila. The instrument was tested using Exploratory Factory Analysis (EFA) and the reliability of items, Cronbach’s Alpha was also established with an index of .88 that shows good reliability. Out of 66 items, 31 remained significant and stable in the four factors of self-efficacy with a consistency value Cronbach’s Alpha of .82. Given the results for the acceptable items in EFA, it was tested using a Confirmatory Factor Analysis (CFA). The goodness of fit based on the RMS standardized residual (RMS=0.070) showed less error having a value closer to .01. The Noncentrality fit indices values show good fit for self-efficacy with four-factor (Steiger-Lind RMSEA = 0.60, Population Gamma Index= 0.910, Adjusted Population Gamma Index= 0.896).